FAKTOR-FAKTOR YANG MEMENGARUHI KEJADIAN SINDROM PRAMENSTRUASI PADA MAHASISWI FAKULTAS KEDOKTERAN UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAKARTA - Farhani Miftahurrahmi (2022)
Premenstrual syndrome (PMS) is a combination of physical and psychological symptoms that occur during the luteal phase of the menstrual cycle. Symptoms that arise such as headache, constipation, depression, decreased concentration power, edema, breast enlargement, weight gain, emotional instability, and changes in appetite. The incidence of PMS can have an impact on daily activities such as disrupting learning concentration, causing decreased learning productivity. This study aimed to analyze the factors that associated PMS among students of the Faculty of Medicine, Universitas Pembangunan Nasional Veteran Jakarta (FK UPNVJ). This research is observational analytical with cross-sectional study among students of FK UPNVJ with a total of 44 respondents. The questionnaire consisted of self-data, Shortened Premenstrual Assessment Form (SPAF), menarche age, family history, Depression Anxiety Stress Scale 42 (DASS 42), and Pittsburgh Sleep Quality Index (PSQI). The results showed that there was relation between stress degree and the incidence of PMS with a value of p = 0.04. Academic and non-academic activities affect student stress degree. Stressors that affect students such as academic assignments, final exams, social issues, and financial problems.